Regorafenib‐induced hyperammonemic encephalopathy. (7th April 2014) - Kuo, J. C.; Parakh, S.; Yip, D.
Summary What is known and objective Regorafenib improves progression‐free survival as a late‐line treatment for patients with metastatic gastrointestinal stromal tumour (GIST). As a multitargeted tyrosine kinase inhibitor (TKI), the expected adverse events of regorafenib are similar to those reported with imatinib, sunitinib or sorafenib. We report the first case of hyperammonemic encephalopathy related to regorafenib in a patient with metastatic GIST. Case summary A 61‐year‐old man maintained on regorafenib for metastatic GIST presented with acute confusion. Discontinuation of regorafenib led to complete resolution of confusion, which later recurred with hyperammonemia on recommencing regorafenib. Cessation of regorafenib and normalization of hyperammonemia then resulted in resolution of confusion. What is new and conclusions Regorafenib withdrawal and recommencement had influenced the confusional state and hyperammonemia in this patient. There is a probable relationship between regorafenib and metabolic encephalopathy. There are case reports of similar encephalopathy thought to be induced by other multitargeted TKI, and, as such, a class effect could be postulated.